Jurisdiction over electronic contracts in cross-border tourism disputes between China and Kazakhstan: Dilemma and path - Ming-zhe, Su; Geng, Cheng; Hong-wei, Wang (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This article discusses the jurisdiction of electronic contracts in cross-border tourism between China and Kazakhstan, and analyzes its theoretical basis, practical difficulties, and breakthrough paths. The principles of freedom of contract, closest connection, and party autonomy in private international law provide theoretical support for cross-border contract jurisdiction, but the differences between China and Kazakhstan in legal systems and industry characteristics have led to intensified jurisdictional conflicts. In reality, the two countries have significant differences in terms of the elements of electronic contract formation, consumer protection, data sovereignty, fragmentation of the place of performance, and identification of electronic evidence. To break through the dilemma, this article proposes three paths: international commercial arbitration, adjustment of domestic judicial interpretations and optimization of bilateral judicial cooperation, including measures such as promoting the alignment of judicial interpretations, establishing a system for mutual recognition of electronic evidence, strengthening the binding force of model contracts, innovating dispute resolution mechanisms and introducing third-party guarantee mechanisms. Through collaborative governance, China and Kazakhstan can build stable and efficient jurisdiction rules to provide legal guarantees for the healthy development of cross-border tourism.